2017
DOI: 10.5897/ajar2016.11931
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield of baby corn as influenced by nitrogen topdressing

Abstract: Baby corn maize (Zea mays L.) is a highly profitable alternative to farmers due to its short crop duration, being harvested at the juvenile stage. It demands large amounts of nutrients in a short time, especially nitrogen, which is responsible for the rapid development of crop. This study aimed to evaluate the effect of topdressing application of different doses of nitrogen on the vegetative and spikelet productivity features in the baby corn crop in Janaúba -Minas Gerais. The experiment was laid out in random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Thakur et al (2020) worked on nitrogen levels (75,100, 125 kg ha -1 ) and spacing of crop, which in 125 kg ha -1 nitrogen treatment given maximum yield of baby corn (27.81 q ha -1 ) and harvest index (30.8). Araujo et al (2017) applied various doses of nitrogen (120, 80, 40 and 0 kg ha -1 N) top dressing at 6 leaf stage on baby corn plant. They reported that baby corn's vegetative properties were unaffected by nitrogen topdressing doses but 120 kg ha -1 N gave highest productivity (7815.06 kg ha -1 with husk and 3244.06 kg ha -1 without husk).…”
Section: Effect Of Nitrogen Levels On Baby Corn Yieldmentioning
confidence: 99%
“…Thakur et al (2020) worked on nitrogen levels (75,100, 125 kg ha -1 ) and spacing of crop, which in 125 kg ha -1 nitrogen treatment given maximum yield of baby corn (27.81 q ha -1 ) and harvest index (30.8). Araujo et al (2017) applied various doses of nitrogen (120, 80, 40 and 0 kg ha -1 N) top dressing at 6 leaf stage on baby corn plant. They reported that baby corn's vegetative properties were unaffected by nitrogen topdressing doses but 120 kg ha -1 N gave highest productivity (7815.06 kg ha -1 with husk and 3244.06 kg ha -1 without husk).…”
Section: Effect Of Nitrogen Levels On Baby Corn Yieldmentioning
confidence: 99%
“…The by-products of baby corn such as silk, stalk, tassel, and husk can also be used as cattle feed in some areas (Singh et al, 2019). Baby corn is seen as highly profitable for farmers, due to the high demand and its fast harvest at 6-7 weeks after planting (Araújo et al, 2017). The largest consumers of baby corn are the USA, Japan, the Netherlands, and Taiwan (Hossain et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…It had been demonstrated that it adds exceptionally unique flavor to various dishes like pickle, soups, servings of mixed greens and a few Chinese delights. In Chinese, American and European restaurants these are widely used as canned or stir fried vegetable and used as boiled in salt water and can be served with combination of rice, spices and herbs [5]. Baby corn by-products were used by Singh and Kaur (2020) [6] to prepare baby soup mix to alleviate the problem of postharvest losses of an industry.…”
Section: Introductionmentioning
confidence: 99%